Curvilinear Coordinate System Used To Solve Tritium Dispersion In Complex Orographies. - André Meneghetti; Bardo Ernst Josef Bodmann; Marco Tullio Menna De Vilhena (Brazilian Journal of Radiation Sciences)
In this contribution we present progress on research concerning dispersion of tritium around the Angra Nuclear Power Plant (Angra dos Reis, Rio de Janeiro state, Brazil). In particular, we are interested in studying how dispersion behaves in scenarios with complex orography. Our proposal is to transform a problem with curvilinear boundaries into an equivalent problem with plane parallel boundaries. We modify the coordinate system through a diffeomorph conformal transformation. Consequently, the operators of the dynamical equations change according to the additional terms from the affine connection. To define the transformation it is necessary to satisfy strong constraints, i.e., boundaries shall be “smooth”. Even with restrictions, our model can be implemented in several situations. A flat region is a particular case of a curvilinear domain and can be studied, where the height of the boundary layer above rivers, lakes, basins is typically smaller and thus implies a varying boundary layer height, for example. Thus, even in flat regions variations in the boundary layer occur, which characterizes a case of a curvilinear domain. There are several nuclear power plants worldwide, that are located in mountainous regions, as for example in Japan and Brazil.We present a simulation of tritium dispersion specifically in the area where the Angra 2 Nuclear Power Plant is located and where the relief is characterized by a considerable complexity. With the intention of showing that the methodology is consistent, we will consider only the variation of the relief.